Virtual Screening of Inhibitor Compounds for HL-60 Cell Line Using QSAR and Molecular Docking Approaches - Putri Handayani, Maulina Surindri; Sudarko, Sudarko; Nugraha, Ari Satia (Universitas Jember, 2024)
Leukaemia is a type of heterogeneous malignancy disease in which the number of immature white blood cells in the bone marrow is increased or poorly differentiated. Inhibitors of HL-60 cell line are important drugs in the treatment of leukaemia. This study aims to identify potential inhibitors for HL-60 leukaemia cells using virtual screening with QSAR and molecular docking approaches. The best QSAR model obtained was the model with R2 testing value of 0.72. The best model was applied to the Enamine database, obtained 3,841,278 compounds with pIC50 above 9 were clustered to end up with 50 inhibitor candidate compounds. The compounds were further studied through molecular docking against CDK- 2 and BCL-2 target proteins with binding free energy analysis. Screened compounds have high inhibitory potential against CDK-2 and BCL-2 target proteins in HL-60 cells which can be proposed as potential inhibitors of HL-60 cells. These compounds can be further tested for the development of more effective antileukaemia drugs.